Т. 4; Сборник аннотированных фольклорных и бытовых текстов обско-енисейского языкового ареала - Фильченко А. Ю. Андрей Юрьевич; Потанина О. С. Ольга Сергеевна; Фелан П. М. Пол Мэтью; Варда В. Е. Виктор Евгеньевич; Курганская Ю. В. Юлия Васильевна; Крюкова Е. А. Елена Александровна; Байдак А. В. Александра Владимировна; Ильяшенко И. А. Ирина Анатольевна; Ковылин С. В. Сергей Васильевич; Максимова Н. П. Наталья Петровна; Вагнер-Надь Б. Беата; Брыкина М. Ю. Мария Юрьевна; et al. (Изд-во Вайар, 2015)
Заглавие с экрана